Combination of different fecal immunochemical tests in colorectal cancer screening: any gain in diagnostic performance? - Gies, Anton; Cuk, Katarina; Schrotz-King, Petra; Brenner, Hermann (Cancers, 2019)
A variety of fecal immunochemical tests (FITs) are used for colorectal cancer screening. FIT performance could be improved further. It is unclear, whether the combination of different FITs with different analytical characteristics (such as, different antibodies for the detection of fecal hemoglobin) can yield a better diagnostic performance. Fecal samples were obtained from 2042 participants of screening colonoscopy. All participants with advanced neoplasm (AN, colorectal cancer (n = 16) or advanced adenoma (n = 200)) and 300 randomly selected participants without AN were included. Nine quantitative FITs were evaluated simultaneously. Sensitivity and specificity was calculated for single tests (n = 9) and for their pairwise test combinations (n = 36) (requiring either both FITs (P) or at least one FIT (P+) to be positive for defining a positive test result). Mean age of the participants (n = 516) was 63 (range: 50–79) years and 56% were men. At cutoffs yielding a specificity of 96.7% for single FITs, the median gain in specificity by P++ combination was +1.0%, whereas the median loss in sensitivity for AN was −4.2%. For P+ combination the median gain in sensitivity for AN was +2.8%, at a prize of median loss of −1.0% of specificity. Combinations of different FITs do not yield any relevant gain in diagnostic performance.
Gesehen am 25.01.2019